An examination of diversification benefits under different market conditions / Rohit Kishore - Kishore, Rohit (2012)
This study examines risk diversification benefits achievable to the Australian mixed-asset portfolio of stocks and bonds from inclusion of listed property trusts (LPTs) as the third asset class in the portfolio. There is available considerable literature showing evidence of added risk diversification benefit from inclusion of property assets within the mixed-asset investment portfolio. This study extends knowledge in this area by examining whether the level of diversification benefit varies under different market conditions, that is, in a rising, static and falling market conditions. The three assets forming the portfolio: listed company shares, bonds and listed property trusts are represented by Australian share market index, bond index and listed property trust index respectively. Methods used for the analysis include rolling and recursive correlation and modern portfolio theory (MPT). Following MPT theory, several efficient frontiers are constructed to measure the different levels of diversification benefits under the three different market conditions. The study finds strong evidence to suggest that correlation of LPTs with stocks and bonds increase during the falling market conditions. Increasing correlation suggests that diversification strategies including LPTs should be reviewed under different market conditions. In particular during the falling market condition, the market volatility is highest and diversification of risk most required. However, the results of increasing correlation during this condition in fact suggest reduction in the diversification benefits. One of the important implications of this finding therefore is that investment strategies should carefully analyse the strategic levels of allocations to LPTs, in order to maximise diversification benefits when it is most needed during the falling market condition.